Varenicline decreases nicotine but not alcohol self-administration in genetically selected Marchigian Sardinian alcohol-preferring (msP) rats. (1st November 2015) - Scuppa, Giulia; Cippitelli, Andrea; Toll, Lawrence; Ciccocioppo, Roberto; Ubaldi, Massimo
Highlights: Alcohol and nicotine are largely co-abused. Varenicline is a first-line treatment option for nicotine dependence. Varenicline attenuates nicotine self-administration in alcohol-preferring animals. Varenicline fails to reduce ethanol intake in alcohol-preferring animals. When alcohol and nicotine are co-used, varenicline's effect is restricted to nicotine. Abstract: Background: Alcohol and nicotine are largely co-abused. Here, we investigated whether concurrent exposure to both addictive drugs influences each other's consumption and whether varenicline attenuates alcohol consumption in the presence of nicotine. Methods: Marchigian Sardinian alcohol-preferring (msP) rats trained to simultaneously self-administer oral alcohol (10% v/v) and intravenous nicotine (30 μg/kg/inf) were used. Additional groups of rats were trained to self-administer either alcohol or nicotine. Further, msP rats were also trained to self-administer nicotine followed by 22-h/day access to alcohol and water in a two bottle free choice paradigm or water alone. The effects of varenicline (0.0, 0.3, 1.0, 3.0 mg/kg, p.o.) on alcohol and nicotine consumption were tested. Results: In a self-administration paradigm, msP rats showed a significantly high level of alcohol and nicotine intake when the drugs were administered alone. However, when access to both drugs occurred concomitantly, the number of nicotine infusions self-administered was significantly decreased. Nicotine self-administration was markedly reduced by varenicline regardless of whether it was self-administered alone or concurrently with alcohol. In a two bottle choice test, varenicline significantly decreased nicotine self-administration but had no influence on alcohol consumption. Conclusion: Varenicline is highly efficacious in decreasing nicotine self-administration either alone or in combination with alcohol. However, varenicline failed to influence both operant responding for alcohol and home-cage alcohol drinking in msP animals. Taken together, our findings suggest that the effects of varenicline could be specific to nicotine under conditions where excessive alcohol drinking is facilitated by genetic factors as in msP rats.